Opening the Research Text Critical Insights and In(ter)ventions into Mathematics Education - de Freitas, Elizabeth; Nolan, Kathleen (Mathematics Education Library, 2008)
Opening the Research Text Critical Insights and In(ter)ventions into Mathematics Education Edited by: Elizabeth de Freitas, Adelphi University & University of Prince Edward Island Kathleen Nolan, University of Regina The provocative contributions to Opening the Research Text reflect current interest in the political and cultural underpinnings of mathematics education. With 22 contributors including both established researchers and newcomers, this innovative research-oriented volume challenges traditional theories and "comforting narratives" of pedagogy through realistic, non-linear scenarios reflecting the ambiguities and power relationships of the classroom. By alternating research chapters with inventive responses (including poetry, concept mapping, graphic novel, and collage), the editors present theoretical as well as practice-based possibilities in areas as diverse as arts-based inquiry and social justice pedagogy, all in relation to mathematics education. These multiple calls to action will inspire readers to: Rethink the accessibility and impact of their classroom work. Consider the value of poststructuralist strategies to curriculum theory. Explore alternate research paradigms in mathematics education. Trace the intersections of power, economics and mathematics. Critically examine the discourse of school mathematics and policy documents. Engage in self-study, writing their own stories of insight and in(ter)vention. Opening the Research Text asks teachers, researchers and scholars to add to the dialogue that is transforming the mathematics education field, and leads new educators toward insights into their careers and the students and communities they serve. Additionally, the book can be a primary graduate or supplementary undergraduate text in education or mathematics education.